2013
DOI: 10.11646/zootaxa.3619.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of the European sand gobies in Gobionellidae and characterization of gobionellid lineages (Gobiiformes: Gobioidei)

Abstract: The Mediterranean, northeastern Atlantic, and inland freshwaters of Europe and the Ponto-Caspian region host a distinct fauna of gobiiform fishes, including the sand gobies (Pomatoschistus Gill and related genera), all of which have been clas-sified in the most diverse goby group, the family Gobiidae. Recent molecular phylogenetic analyses have suggested that the sand gobies are not gobiids, and are instead part of their sister clade Gobionellidae (Thacker and Roje 2011). Phylo-genetic analysis of Pomatoschist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
2
35
1
1
Order By: Relevance
“…S1 in Appendix S2). Phylogenetic relationships recovered here are not significantly different from those shown in Thacker & Roje (), Thacker (, ), or Agorreta et al . ().…”
Section: Resultssupporting
confidence: 55%
“…S1 in Appendix S2). Phylogenetic relationships recovered here are not significantly different from those shown in Thacker & Roje (), Thacker (, ), or Agorreta et al . ().…”
Section: Resultssupporting
confidence: 55%
“…Molecular phylogenetic analyses of gobioids have confirmed the composition of families in the clade (Agorreta et al, 2013;Tornabene et al, 2013), and have identified several well-supported lineages within the most species-rich families, Gobionellidae and Gobiidae (Thacker and Roje, 2011;Agorreta et al, 2013;Thacker, 2013).…”
mentioning
confidence: 86%
“…() placed order Gobiiformes in the supra‐ordinal group Gobiomorpharia. Phylogenetic relationships within Gobioidei are also still not fully resolved and results of some recent studies of the Gobioidei differ from studies of just European lineages (Thacker, , ; Thacker & Roje, ; Agorreta et al, ; Tornabene et al, ).…”
Section: Introductionmentioning
confidence: 92%